Transformation of Consumer’s Coffee Consumption Behaviour in Batam - Fasha, Andina; Anggraini, Ratih; Purwianti, Lily; Ramadani, Arienda Gitty (Penerbit Goodwood, 2024)
Purpose: The transformation that has occurred in coffee consumption behavior is inseparable from the development of globalization which makes people behave consumptively. This will result in various changes to coffee consumption behavior in the people of Batam City. This study aims to discover coffee consumption behavior, trends, lifestyles, and preferences, where people have the habit of consuming coffee in dine-in coffee shops. But as it evolved, it turned into a coffee takeaway. Methodology/approach: This research uses a quantitative approach that aims to explore the causes related to changes in coffee consumption behavior. Data collection was carried out by purposive sampling with a total of 100 samples. Results/findings: Based on the analysis, five hypotheses were accepted, and two hypotheses were rejected, namely trends, lifestyles, and preferences that had a positive effect on consumption behavior. Preferences can mediate trends in coffee consumption behaviour, while preferences are not able to mediate the influence between lifestyle and consumption behaviour and there is no influence between lifestyle and coffee consumer preferences. Limitations: This study has limitations in that the transformation of coffee consumer behavior was only conducted in Batam City, so there may be differences of opinion if conducted in other cities due to different demographics, cultures, and lifestyles of the people in those cities. Contribution: The results of this study contribute to a deeper understanding of the dynamics of consumer behavior in consuming coffee, providing practical implications in the retail field of coffee business and valuable insights for academics.